Efficient and Full‐Spectrum Photothermal Dehydrogenation of Ammonia Borane for Low‐Temperature Release of Hydrogen. (20th November 2020) - Huang, Hanlin; Wang, Cong; Li, Qi; Wang, Ruiqi; Yang, Yuying; Muhetaer, Aidaer; Huang, Fuqiang; Han, Bing; Xu, Dongsheng
Abstract: Efficient hydrogen release from ammonia borane (AB) with a striking hydrogen content (19.6 wt%) via thermolysis provides a promising pathway for on‐board applications utilizing hydrogen energy. However, the sluggish kinetics at low temperatures and high energy consumption of thermal dehydrogenation are major obstacles for hydrogen release from AB. Herein, a novel solar‐driven strategy for hydrogen production from AB at low temperature is proposed, in which Ti2 O3 is utilized as a full‐spectrum light absorber for photothermal‐activating solid‐state AB reactants to produce hydrogen. Through a reduction transformation method, nanoscale Ti2 O3 particles with high chemical stability and narrow band gap are prepared, realizing a rapid production of 2.0 equivalents of hydrogen from AB at ambient temperature, with an excellent recyclable and full‐spectrum‐responsive photothermal dehydrogenation. Importantly, a record high photothermal activation efficiency of 35% is achieved with nanoscale Ti2 O3 particles due to an enhanced local photothermal effect contributed by improved light absorption and decreased thermal conduction. Moreover, assisted with CuCl2 promoter, a release of 2.0 equivalents of hydrogen under 1.0 solar irradiation at 70 °C is successfully achieved, revealing its potential applications in practical vehicles based on proton exchange membrane fuel cells. Abstract : Full‐spectrum, photothermal‐activated efficient H2 production from ammonia borane at room temperature is proposed, utilizing nanostructured Ti2 O3 with a narrow band gap, achieving a high photothermal activation efficiency (35%). Combined with an efficient promoter, 2.0 equivalents of H2 production at 70 °C (simulates the working temperature of proton exchange membrane fuel cells) only requires an ambient light irradiation (1.0 sun).